1993
DOI: 10.1007/bf00164465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the anaerobic dechlorination of chlorophenols in a defined medium

Abstract: Anaerobic dehalogenation of aromatic compounds is a well-documented phenomenon. However, the effects of operating parameters such as pH have received little attention despite their potential impact on treatment processes using dehalogenating organisms. In this work the effect of pH on the dehalogenation of 2,4,6-trichlorophenol (2,4,6-TCP) was studied using defined media containing one of several non-fermentable buffering agents (MOPS, TRICINE, BI-CINE, CHES), and no chloride ions. The dechlorination process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…Because no inhibitory effect was apparent this time, the Monod model [Eq. (4)] was used to regress the data. The corresponding values of pmax and K, are also given in Table I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because no inhibitory effect was apparent this time, the Monod model [Eq. (4)] was used to regress the data. The corresponding values of pmax and K, are also given in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…In the first type, p increased as a function of S and approached an asymptotic value for large values of S. The data showing this trend were analyzed using a Monod kinetic expre~sion~*~': (4) where pmax and Ks were obtained from a nonlinear regression of the experimental values using a modified Levenberg-Marquardt method. 1671' This approach was preferred to the traditional Lineweaver-Burke plotting5 of Up vs. 1/S that puts too much emphasis on the low-substrateconcentration data points.…”
Section: Determination Of Kinetic Parametersmentioning
confidence: 99%
“…Analytical Method A Waters HPLC system was used for the determination of phenol and all chlorophenols. Details of the analytical procedure are reported elsewhere Armenante et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The rate of dechlorination under such conditions is actually greatest for more heavily chlorinated compounds, and it slows down as the chlorophenoi molecules become more dechlorinated. Previous investigations have shown that the aromatic ring is not attacked under anaerobic conditions (Kafkewitz et al, 1992;Armenante et al, 1993;Togna et aL, 1995). However, to date little quantitative information on the dehaiogeuation rates of chlorophenols by anaerobic cultures is available, and no kinetic parameters have been obtained.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation